2022
DOI: 10.1007/s10162-022-00878-8
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Polarity Minimizes Facial Nerve Stimulation as a Side Effect of Cochlear Implantation

Abstract: One severe side effect of the use of cochlear implants (CI) is coincidental facial nerve stimulation (FNS). Clinical methods to alleviate FNS range from the reprogramming of processor settings to revision surgery. We systematically assessed different changes in CI stimulation modes that have been discussed in the literature as “rescue factors” from FNS: electrode configuration (broad to focused), pulse shape (symmetric biphasic to pseudo-monophasic), and pulse polarity (cathodic to anodic). An FNS was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“… 16 Meanwhile, at Cochlear Corporation, a change in the stimulation mode was observed, changing the mode from monopolar to bipolar, allowing a more restricted electric field, dispersing the electric current less, and being able to avoid and/or decrease FNS. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Meanwhile, at Cochlear Corporation, a change in the stimulation mode was observed, changing the mode from monopolar to bipolar, allowing a more restricted electric field, dispersing the electric current less, and being able to avoid and/or decrease FNS. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 Meanwhile, at Cochlear Corporation, a change in the stimulation mode was observed, changing the mode from monopolar to bipolar, allowing a more restricted electric field, dispersing the electric current less, and being able to avoid and/or decrease FNS. 17 In our study, data regarding the recognition of sentences in different conditions were collected. The average of speech recognition in open presentation before the identification of the FNS was 57,5% of correct answers; however, after the identification of the FNS and adjustments had been made to avoid extra hearing aid stimulation, the average speech recognition was 83,7% correct.…”
Section: Discussionmentioning
confidence: 99%
“…Both return current via intracochlear electrodes. A study investigating the effects of different grounding strategies on FNS efficacy, conducted using 204 electrically evoked compound action potential (eCAP) input/output functions recorded from 33 ears of 26 guinea pigs, revealed that-for biphasic pulses-the broad-MP grounding was associated with a high occurrence of FNS (65%), while bipolar and an experimental tripolar configuration (expected to be the most focused) generated only 20% and 2% of FNS occurrences, respectively [15].…”
Section: Groundingmentioning
confidence: 99%